Immune responses following 3rd and 4th doses of heterologous and homologous COVID-19 vaccines in kidney transplant recipients. (November 2022) - Thomson, Tina; Prendecki, Maria; Gleeson, Sarah; Martin, Paul; Spensley, Katrina; De Aguiar, Rute Cardoso; Sandhu, Bynvant; Seneschall, Charlotte; Gan, Jaslyn; Clarke, Candice L.; Lewis, Shanice; Pickard, Graham; et al.
Summary: Background: Solid organ transplant recipients have attenuated immune responses to SARS-CoV-2 vaccines. In this study, we report on immune responses to 3rd- (V3) and 4th- (V4) doses of heterologous and homologous vaccines in a kidney transplant population. Methods: We undertook a single centre cohort study of 724 kidney transplant recipients prospectively screened for serological responses following 3 primary doses of a SARS-CoV2 vaccine. 322 patients were sampled post-V4 for anti-spike (anti-S), with 69 undergoing assessment of SARS-CoV-2 T-cell responses. All vaccine doses were received post-transplant, only mRNA vaccines were used for V3 and V4 dosing. All participants had serological testing performed post-V2 and at least once prior to their first dose of vaccine. Findings: 586/724 (80.9%) patients were infection-naïve post-V3; 141/2586 (24.1%) remained seronegative at 31 (21-51) days post-V3. Timing of vaccination in relation to transplantation, OR: 0.28 (0.15-0.54), p=0.0001; immunosuppression burden, OR: 0.22 (0.13-0.37), p<0.0001, and a diagnosis of diabetes, OR: 0.49 (0.32-0.75), p=0.001, remained independent risk factors for non-seroconversion. Seropositive patients post-V3 had greater anti-S if primed with BNT162b2 compared with ChAdOx1, p=0.001. Post-V4, 45/239 (18.8%) infection-naïve patients remained seronegative. De novo seroconversion post-V4 occurred in 15/60 (25.0%) patients. There was no difference in anti-S post-V4 by vaccine combination, p=0.50. T-cell responses were poor, with only 11/54 (20.4%) infection-naive patients having detectable T-cell responses post-V4, with no difference seen by vaccine type. Interpretation: A significant proportion of transplant recipients remain seronegative following 3- and 4- doses of SARS-CoV-2 vaccines, with poor T-cell responses, and are likely to have inadequate protection against infection. As such alternative strategies are required to provide protection to this vulnerable group. Funding: MW/PK received study support from Oxford Immunotec.